Manajemen Kepala Sekolah dalam Pengembangan Sistem Pelayanan Perpustakaan di Sekolah Menengah Atas Negeri 4 Tebo - Dwi Seftiawati; Sumirah Sumirah; Aris Dwi Nugroho (JMiE (Journal of Management in Education), 2025)
This study aims to analyze the principal’s management in developing the library service system at Senior High School 4 Tebo. A qualitative descriptive approach was employed in this research. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The findings indicate that the principal has implemented management functions in library management, including strategic planning, service organization, program implementation, and evaluation of collection development and library layout. However, the development of the library service system has not been fully optimized due to limitations in human resource competencies, technological infrastructure, and budget availability. This study emphasizes that the effectiveness of school library service development is strongly influenced by the principal’s managerial leadership that is adaptive, aligned with national standards, and oriented toward improving educational quality and strengthening the school literacy culture.